Relative control [videorecording (DVD)] - Davis, Charlene D.; Polo, Teri, 1969-; McDade, Patrick F.; Schaerer, Alice (Gravitas Ventures, 2025)
A middle-aged, type-A attorney's life spirals as she juggles her handful of an ex-cop father, forgetful mother, unemployed son, a reignited romance, and a hostile takeover in the biggest corporate control battle of her career.